2015
DOI: 10.1037/ort0000087
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational effects of parental substance-related convictions and adult drug treatment court participation on children’s school performance.

Abstract: Objective This study examined the intergenerational effects of parental conviction of a substance-related charge on children’s academic performance and, conditional on a conviction, whether completion of an adult drug treatment court (DTC) program was associated with improved school performance. Method State administrative data from North Carolina courts, birth records, and school records were linked for 2005–12. Math and reading end-of-grade test scores and absenteeism were examined for 5 groups of children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 78 publications
(132 reference statements)
1
12
0
Order By: Relevance
“…The results of this study complement two other studies that demonstrated that the children of drug treatment participants, and the broader population of individuals with convictions who are not served by drug treatment courts, are at an elevated risk of being involved with child protective services (Gifford et al 2016) and of having poor academic outcomes (Gifford et al 2015). Given the enormous societal costs of involvement with child protective services, being arrested as a youth, and poor school outcomes (Cohen 1998; Cohen et al 2010; Fang et al 2012; Sum et al 2009), learning how to implement effective prevention strategies is warranted.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The results of this study complement two other studies that demonstrated that the children of drug treatment participants, and the broader population of individuals with convictions who are not served by drug treatment courts, are at an elevated risk of being involved with child protective services (Gifford et al 2016) and of having poor academic outcomes (Gifford et al 2015). Given the enormous societal costs of involvement with child protective services, being arrested as a youth, and poor school outcomes (Cohen 1998; Cohen et al 2010; Fang et al 2012; Sum et al 2009), learning how to implement effective prevention strategies is warranted.…”
Section: Discussionsupporting
confidence: 75%
“…Such stress can take an emotional toll and can increase conflict in the home (Conger et al 1994). Parental criminal involvement has been associated with increased risk of children’s mental health problems (Dallaire and Wilson 2010; Phillips et al 2002), child protective services involvement (Gifford et al 2016), and lower school performance (Gifford et al 2015). Moreover, a substantial body of research has found that criminality runs in families—particularly from fathers to sons (Bijleveld and Wijkman 2009; Farrington et al 2001; Hjalmarsson and Lindquist 2012; Junger et al 2013; Rowe and Farrington 1997; van de Rakt et al 2009, 2010; van de Weijer et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This result coincides with findings from another study examining the impact of adult DTCs on child educational outcomes. In this study, using the same data, we could not detect an intergenerational benefit on children’s school performance resulting from parents’ participation in an adult DTC (Gifford, Sloan, Eldred, & Evans, 2015). In contrast to our findings on adult DTCs, family DTCs do have a significant impact on the well-being of children.…”
Section: Discussionmentioning
confidence: 61%
“…We use data from the Swedish general population to examine whether exposure to neighborhood deprivation during two key developmental periods (early and middle childhood) is associated with school achievement in adolescence and later difficulties with social functioning in emerging adulthood, and whether these, in turn, are predictive of onset of AUD in adolescence and emerging adulthood. Our hypothesis is that, after accounting for parental SES and parent externalizing behavior, another key predictor of child academic problems (Berg et al, 2016; Gifford et al, 2015) and substance use (Chassin et al, 1999; Kendler et al, 2013; Kendler et al, 2016c), exposure to neighborhood deprivation during early and middle childhood will be associated with lower school achievement in adolescence, as well as reduced social functioning in young adulthood, leading to subsequent development of AUD. We use stratified models to assess these pathways separately for men and women, as some research suggests sex differences in the effects of early adversity on later outcomes (Johansson et al, 2015; Kroneman et al, 2004).…”
Section: Current Studymentioning
confidence: 99%